ECOLOGICAL AND SOCIO-ECONOMIC CONSEQUENCES OF THE SARDOBA RESERVOIR DISASTER (2020): A GEOGRAPHICAL ANALYSIS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
On May 1, 2020, the breach of the Sardoba reservoir dam located in the Sardoba district of Sirdarya region became one of the largest man-made disasters in the years of Uzbekistan's independence. This article provides a comprehensive scientific analysis of the geographical, ecological, and socio-economic consequences of the disaster. The study examines the geographical characteristics of the flooded areas, damage to soil and groundwater, and the impact on agriculture, infrastructure, and the livelihoods of the population. The analysis shows that the effects of the disaster spread beyond Sardoba district to Sirdarya region of Uzbekistan and Turkistan region of Kazakhstan, causing serious ecological and social consequences on a regional scale. The article develops scientific recommendations for preventing the disaster and avoiding the recurrence of such disasters.